2014
DOI: 10.1097/jcp.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Add-On Low-Dose Memantine on Cytokine Levels in Bipolar II Depression

Abstract: Memantine, a noncompetitive N-methyl-d-aspartate receptor antagonist with a mood-stabilizing effect, and an association between bipolar disorder and proinflammatory cytokine levels have been reported. Whether adding-on memantine would reduce cytokine levels and is more effective than valproic acid (VPA) alone in bipolar II disorder was investigated. A randomized, double-blind, controlled, 12-week study was conducted. Patients undergoing regular VPA treatments were randomly assigned to a group: VPA + memantine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 58 publications
1
22
0
1
Order By: Relevance
“…A non-significant reduction in sIL-6R and sIL-2R was observed, but IL-6 levels were unaltered despite significant improvement of clinical symptoms. A study in patients with bipolar depression could not find an effect of a 12-week valproate trial on the levels of IL-1β, IL-6, IL-8 and TNF-α (Lee et al, 2014). We found no studies reporting on the effect of carbamazepine or lamotrigine on cytokine levels in BD.…”
Section: Anti-epilepticsmentioning
confidence: 90%
See 1 more Smart Citation
“…A non-significant reduction in sIL-6R and sIL-2R was observed, but IL-6 levels were unaltered despite significant improvement of clinical symptoms. A study in patients with bipolar depression could not find an effect of a 12-week valproate trial on the levels of IL-1β, IL-6, IL-8 and TNF-α (Lee et al, 2014). We found no studies reporting on the effect of carbamazepine or lamotrigine on cytokine levels in BD.…”
Section: Anti-epilepticsmentioning
confidence: 90%
“…Two studies report on the effect of valproate on cytokine levels in patients with BD (Lee et al, 2014;Maes et al, 1995a). In 10 patients with mania, the effect of a 2-week trial with valproate on IL-6, sIL-2R and sIL-6R levels was evaluated (Maes et al, 1995a).…”
Section: Anti-epilepticsmentioning
confidence: 99%
“…A number of agents do not have sufficient data to warrant specific recommendations for BDII depression, including cranial electrotherapy stimulation (CES),479 dextromethorphan + quinidine,480 light therapy,481, 482, 483, 484, 485 lisdexamfetamine (adjunctive),300 olanzapine,486 pioglitazone,302 adjunctive pregnenolone,306 celecoxib,297 levetiracetam,487 adjunctive lisdexamfetamine,300 s‐adenosylmethionine,488, 489, 490 acetyl‐ l ‐carnitine + alpha‐lipoic acid,491 adjunctive modafinil,268 rTMS,275, 492, 493 and memantine 494…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…Some studies have reported that abnormal levels of cytokines such as tumor necrosis factor-α, IL-8, and IL-10 play an important role in the pathophysiology of BD. [7,8] Taken together, both IBS and BD may, at least partially, share a similar mechanism of pathophysiology. Therefore, it is hypothesized that they may have a similar comorbidity rate.…”
Section: Introductionmentioning
confidence: 99%